Public infrastructure, location of private schools and primary school attainment in an emerging economy - Sarmistha Pal (Institute for the Study of Labor (IZA), 2009)
The paper argues that access to public infrastructure plays a crucial role on the presence of private schools in a community, as it could not only minimise the cost of production, but also ensure a high return to private investment. Results using community, school and child/household-level PROBE survey data from five north Indian states provide some support to this central hypothesis: even after controlling for all other factors, access to village infrastructural facilities is associated with a higher likelihood of having a private school in the community. This is also corroborated by an analysis of household demand for private schools. The paper concludes by examining the effect of private school presence on year 5 pass rates: while all-school pass rates are significantly higher in villages with a private school, private school presence fails to have significant effect on local state school pass rates.
Keywords: I20; I30; O15; P36; 330; School privatisation; school choice; school attainment; local public infrastructure; failing state schools; simultaneity bias; instrumental variable; Privatschule; Allgemeinbildende Schule; Dienstleistungsqualität; Kommunale Infrastruktur; Standort; Indien